Design of 4-stage Marx generator using gas discharge tube - Wijono Wijono; Zainul Abidin; Waru Djuriatno; Eka Maulana; Nola Ribath (Institute of Advanced Engineering and Science, 2021)
In this paper, a Marx generator voltage multiplier as an impulse generator made of multi-stage resistors and capacitors to generate a high voltage is proposed. In order to generate a high voltage pulse, a number of capacitors are connected in parallel to charge up during on time and then in series to generate higher voltage during off period. In this research, a 6kV Marx generator voltage multiplier is designed using gas discharge tube (GDT) as an electronic switch to breakdown voltage. The Marx generator circuit is designed to charge the storage capacitor for high impulse voltage and current generator applications. According to IEC 61000-4-5 class 4 standards, the storage capacitor must be charged up to 4 kV. The results show that the proposed Marx generator can produce voltages up to 6.8 kV. However, the storage capacitor could be charged up to 1 kV, instead of 4 kV in the standard. That is because the output impulse voltage has narrow time period.